2013
DOI: 10.1073/pnas.1312782110
|View full text |Cite
|
Sign up to set email alerts
|

Ferrous iron-dependent drug delivery enables controlled and selective release of therapeutic agents in vivo

Abstract: The precise targeting of cytotoxic agents to specific cell types or cellular compartments is of significant interest in medicine, with particular relevance for infectious diseases and cancer. Here, we describe a method to exploit aberrant levels of mobile ferrous iron (Fe II ) for selective drug delivery in vivo. This approach makes use of a 1,2,4-trioxolane moiety, which serves as an Fe II -sensitive "trigger," making drug release contingent on Fe II -promoted trioxolane fragmentation. We demonstrate in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…In previous studies, we demonstrated the utility of the TRX scaffold by efficiently and selectively delivering antimalarial payloads to ferrous iron/heme rich compartments of the malaria parasite, both in vitro 30,31 and in vivo. 32,33 …”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we demonstrated the utility of the TRX scaffold by efficiently and selectively delivering antimalarial payloads to ferrous iron/heme rich compartments of the malaria parasite, both in vitro 30,31 and in vivo. 32,33 …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Our designs in particular involve embedding a masked retro-Michael linker in an arterolane-like scaffold. [6][7][8] Intra-parasitic reduction of the endoperoxide bond in such systems (e.g., 3) serves to unmask a ketone and reveal the competent retro-Michael substrate 4, which then undergoes traceless release of a 3"-carbamate-tethered payload (Scheme 1). The key reduction step is widely thought [10][11][12][13] to involve Fenton-type reaction in the parasite digestive vacuole (DV), promoted by iron(II)-heme that is liberated during the catabolism of hemoglobin.…”
mentioning
confidence: 99%
“…1820 Once revealed, this ketone intermediate undergoes spontaneous β-elimination and decarboxylation to release a drug species attached at the β-position. Thus, iron(II)-dependent drug delivery is achieved by coupling trioxolane fragmentation and β-elimination chemistries.…”
mentioning
confidence: 99%